Effects of CTL and Inquiry-Based Learning Through Lesson Study on Scientific Literacy and Science Achievement - Mardianti, Yuli; Nuraini, Nuraini; Khairul Wazni , Muhammad (IJE : Interdisciplinary Journal of Education, 2026)
This study examines the effects of Contextual Teaching and Learning (CTL) and Inquiry learning models implemented through Lesson Study on students’ scientific literacy and science achievement. A quasi-experimental design with a pretest–posttest control group approach was employed. The participants consisted of 54 seventh-grade students from SMP Negeri 1 Sikur, divided into two groups: the CTL group and the Inquiry group. Data were collected using validated scientific literacy and science achievement tests. Instrument reliability was confirmed using Cronbach’s Alpha (α = 0.82). Data were analyzed using One-Way MANOVA after fulfilling normality and homogeneity assumptions. The results revealed a significant multivariate effect of the learning models on scientific literacy and science achievement (Wilks’ Lambda = 0.742, F(2, 51) = 8.85, p < 0.001, Partial η² = 0.258). Further analysis showed that the Inquiry model resulted in higher mean scores in scientific literacy (M = 84.32, SD = 4.87) and science achievement (M = 83.91, SD = 5.76) compared to the CTL model (scientific literacy: M = 82.15, SD = 5.21; science achievement: M = 80.47, SD = 6.12). These findings indicate that Inquiry learning is more effective in developing higher-order thinking skills, while CTL is effective in enhancing contextual understanding. In conclusion, the integration of CTL and Inquiry through Lesson Study provides meaningful learning experiences and significantly improves students’ scientific literacy and learning outcomes.